Machiavellianism and task-orientated leadership: Moderating effect of job autonomy - Usama Rehman; Mohammad Ghazi Shahnawaz (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
Despite the negative connotation of Machiavellianism, Machs are found in all kinds of organization and at almost all levels. How they function in organizations is worth examining. The present study explored the relationship between Machiavellianism and Task-Oriented Leadership. Job autonomy was also hypothesized as a moderator, impacting the relationship between the two variables. The sample for the study comprised of middle level managers working for different organizations in and around National Capital Region, Delhi, India. Machiavellian Personality scale (MPS), Task oriented Leadership style questionnaire, and Work autonomy scale were used to collect data. The data was analyzed with the help of SPSS V-21 and Process Hayes macros. Results revealed a significant positive relationship between Machiavellianism and Task-oriented leadership. Also, the relationship between the two constructs was moderated by high and average level of job autonomy.
Keywords: 330; Job autonomy; Leadership; Machiavellian leadership; Machiavellianism; Task-oriented leadership